1997
DOI: 10.1016/s0014-5793(96)01416-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel 13 kDa cytoplasmic soluble protein is required for the nucleotide (MgATP) modulation of the Na/Ca exchange in squid nerve fibers

Abstract: The Na/Ca exchange is a highly regulated transport mechanism in which MgATP, a powerful modulatory intracellular substrate, has important implications for its function. As occurs with some preparations, in squid axons, nucleotide regulation is lost after membrane vesicle isolation. This has been a significant obstacle in the biochemical characterization of the MgATP effect. An important clue in solving this long-standing puzzle is presented in this work by showing that prolonged intracellular dialysis of squid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 15 publications
3
50
0
Order By: Relevance
“…This finding led to the idea that a low-molecular-weight cytosolic compound lost during prolonged dialysis was essential, and efforts were started to isolate it. Initially, the starting material was axoplasm extruded from squid giant axons (23); identical results were later obtained by using optic ganglia with the advantage that more material was obtained (94). Figure 25, top, shows the present procedure used for the partial purification of this soluble cytosolic regulatory protein (SCRP).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…This finding led to the idea that a low-molecular-weight cytosolic compound lost during prolonged dialysis was essential, and efforts were started to isolate it. Initially, the starting material was axoplasm extruded from squid giant axons (23); identical results were later obtained by using optic ganglia with the advantage that more material was obtained (94). Figure 25, top, shows the present procedure used for the partial purification of this soluble cytosolic regulatory protein (SCRP).…”
mentioning
confidence: 89%
“…This was circumvented by the development of the inside-out excised giant patch (25-30 m diameter) in cardiac cells (120,123), which allows the study of kinetics and regulatory processes related to the Na ϩ /Ca 2ϩ exchanger function. One main disadvantage is that during the formation of the giant patch, cell components (among them soluble proteins that may be involved in the Na ϩ / Ca 2ϩ exchange regulation) are eliminated (23,94). Finally, substantial progress has been made in the molecular biology of the Na ϩ /Ca 2ϩ exchanger (204).…”
Section: Metabolic and Ionic Regulation Of Namentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to note that a novel 13-kDa cytosolic protein recently isolated from the axoplasm and brain of squid has been shown to be involved in ATP-dependent regulation of NCX-SQ1. 52 Protein kinase A activation by forskolin and/or other reagents has been reported to stimulate activities of cardiac NCX1 expressed in BHK cells 50 and Xenopus oocytes, 24 although the same clone expressed in CCL39 cells is not affected by 8-bromo-cAMP or 8-bromo-cGMP. 48 In frog heart, however, ␤-receptor-dependent or cAMP-dependent stimulation results in the inhibition of NCX activity, in which a novel 9 -amino acid exon of the frog exchanger seems to play a role.…”
Section: Regulationmentioning
confidence: 99%
“…In addition, studies testing the regulation of NCX1.5 by PKA and PKC were reported rarely. Some authors reported that a phosphorylation step could accelerate the transporting function of the Na + /Ca 2+ exchanger [12][13][14] , but others failed to observe the same effect [15,16] .…”
Section: Introductionmentioning
confidence: 99%